Ectopic Ureter Opening into the Seminal Vesical: A Rare Case Report - Dhangar, Dr. Sanjay P. (SP'z Series New Insights on Urology and Urological Research Part I, 2022)
Ureteric abnormalities are rare. Ectopic insertion of the ureter is defined as abnormal insertion of the ureter, usually distal to the trigone into the urethra in male in approximately 50% of cases. Other sites include the seminal vesicle (approximately one-third), vas deferens, bladder neck, prostate and epididymis, while the urethra and vagina are commonly affected in females. Ectopic insertion of the ureter in the genital tract is a rare anomaly. Its incidence is about 1:130000. In contrast to females who come with urinary incontinence, ureteral ectopia in males is often misdiagnosed because of its relatively covert manifestations. Most patients with this anomaly are asymptomatic until the third or fourth decade of life. We present here another case report of this unusual entity and review the clinical characteristics of such cases.